2005
DOI: 10.4049/jimmunol.175.8.5324
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium bovis BCG Attenuates Surface Expression of Mature Class II Molecules through IL-10-Dependent Inhibition of Cathepsin S

Abstract: We have previously shown that macrophage infection with Mycobacterium tuberculosis and M. bovis bacillus Calmette-Guérin (BCG) partially inhibits MHC class II surface expression in response to IFN-γ. The present study examined the nature of class II molecules that do in fact reach the surface of infected cells. Immunostaining with specific Abs that discriminate between mature and immature class II populations showed a predominance of invariant chain (Ii)-associated class II molecules at the surface of BCG-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 67 publications
2
82
0
Order By: Relevance
“…Resting BMMs express very low levels of MHC II on their surface, therefore, the effect of lactoferrin was also examined on IFN-γ activated BCG-infected BMMs. BCG infection of IFN-γ activated BMMs dramatically decreased MHC II + BMMs, a trend that has been previously reported [60][61][62]. The presence of lactoferrin was able to reverse a significant percentage of the BCG induced down regulation of MHC II surface expression, again suggesting that lactoferrin enables activated macrophages to retain their ability to present antigen to T-cells.…”
Section: Discussionsupporting
confidence: 79%
“…Resting BMMs express very low levels of MHC II on their surface, therefore, the effect of lactoferrin was also examined on IFN-γ activated BCG-infected BMMs. BCG infection of IFN-γ activated BMMs dramatically decreased MHC II + BMMs, a trend that has been previously reported [60][61][62]. The presence of lactoferrin was able to reverse a significant percentage of the BCG induced down regulation of MHC II surface expression, again suggesting that lactoferrin enables activated macrophages to retain their ability to present antigen to T-cells.…”
Section: Discussionsupporting
confidence: 79%
“…4B). A considerable body of evidence indicates that IL-10 diminishes macrophage microbicidal capacity (14)(15)(16)(17). In summary, therefore, infection with CH and CAS2 were associated with a pattern of cytokine secretion that would result in phagocyte deactivation favoring the intracellular survival of bacilli.…”
Section: Resultsmentioning
confidence: 99%
“…Other pro-and anti-inflammatory cytokines such as IL-6 and IL-10 also modulate protease activity upwards or downwards, respectively, at least in part by altering endosomal pH [42,43]. In another study, IL-10, produced by BCG infected macrophages, reduced cathepsin S expression levels, thereby overriding the ability of IFN-g to enhance class II MHC levels and promote T-cell recognition of infected cells [44]. However, another study found that IL-10 (and IL-6) enhanced the activity of various cathepsins, including cathepsin S and that IL-6 diminished DM levels [45].…”
Section: Reciprocal Relationships Between Cytokines and Lysosomal Catmentioning
confidence: 98%